2014
DOI: 10.1161/circoutcomes.114.000949
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Utilization of the Emergency Department for Acute Heart Failure Syndrome

Abstract: Background-Although most research on patients with acute heart failure syndrome (AHFS) has focused on readmissions, this may provide an incomplete picture of health-care utilization. We examined the proportion and characteristics of patients with frequent emergency department (ED) visits for AHFS and associated health-care utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…Moreover, the HCUP data are considered accurate and widely used to estimate diagnoses and hospitalization frequency. 7, 10, 36 Second, we identified ID hospitalizations with an ID listed as the primary diagnosis to limit potential misclassification, while this would also have led to an underestimation of ID hospitalizations. Third, the KID contains discharge-level records and not patient-level records.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the HCUP data are considered accurate and widely used to estimate diagnoses and hospitalization frequency. 7, 10, 36 Second, we identified ID hospitalizations with an ID listed as the primary diagnosis to limit potential misclassification, while this would also have led to an underestimation of ID hospitalizations. Third, the KID contains discharge-level records and not patient-level records.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of ED and inpatient data available through the Healthcare Cost and Utilization Project, investigators found that among 113,033 unique patients presenting to the ED for acute HF in Florida and California, 34,793 (31%) had O2 visits for acute HF during a 1-year period. 24 In those 2 states, patients with O2 visits accounted for 55% of all ED visits for acute HF during the same 1-year period. These data underscore the central role of the ED in acute HF care and suggest that programs designed to optimize care for these patients in the ED could reduce rehospitalizations.…”
Section: Post-discharge Emergency Department Carementioning
confidence: 99%
“…Repeated utilization of a healthcare service by a small group of patients is costly 1,2 and also suggests that the medical care those patients are receiving is not adequately addressing their needs. 3,4 Frequent utilization of emergency department (ED) services have been extensively studied, 5–13 in part because ED care is more expensive than primary care and these two types of care may be substitutes for one another in some cases.…”
Section: Introductionmentioning
confidence: 99%